Synthesis of thin-film Ta₂O₅ coatings by reactive magnetron sputtering - Yakovin, S.; Zykov, A.; Dudin, S.; Yefymenko, N. (Вопросы атомной науки и техники, 2016)
The investigation results of optimal conditions for synthesis of thin-film tantalum oxide dielectric coatings using the cluster multipurpose setup are presented. The set-up consist of DC magnetron, ICP source, and mediumenergy ion source. Tantalum oxide was deposited by reactive magnetron sputtering using DC magnetron in atmosphere of argon and oxygen. The oxygen flow was activated by passing trough the ICP source. The described equipment allows independent control of the flows of metal atoms, of reactive particles, and of ions of rare and reactive gas. The current-voltage characteristics of the magnetron discharge were measured as well as teir dependencies on argon pressure and oxygen flow.